Dependence of stress state on the histories of burial, erosion, mechanical properties, pore pressure and faulting. (December 2020) - Harper, Tim
Abstract: Most onshore basins have experienced one or more phases of burial and erosion. The geomechanical evolution of simplified and idealised fault-bounded mudrock basins on crystalline basement subject to burial and erosion cycles is examined numerically. The changes in strains and stress state and the displacements, including bedding slip, which occur with changes of the overlying load, are tracked. Changes of mechanical properties to represent diagenesis are included. Development of the widely reported 'high' horizontal normal stresses results from the changes of vertical load and does not rely directly on applied horizontal tectonic shortening strains. Lateral gradients of normal stress associated with faults are described. The final basin stress state is related to the magnitudes of the burial and erosion, diagenetic or otherwise changes of mechanical properties and pore pressure changes during burial and at depth. The magnitudes of the horizontal stress developed for the 1 km and 2 km burial and erosion cycles tested here exceed the magnitude of the vertical stress for a range of depths extending downwards from the surface unless the horizontal stress is reduced at shallow depths by failure during erosion. Bedding shear instability during erosion, around faults and otherwise, may influence the response to engineering disturbance. Highlights: Development of 'high' horizontal stresses without tectonic horizontal strains. Numerical experiments tracking the geomechanics of burial and erosion. Horizontal stress a function of maximum depth of previous sediment burial or ice load and can exceed vertical stress. Influence of faults and diagenetic alteration of rock properties on horizontal stress. Bedding plane instability.